2018
DOI: 10.1021/acschemneuro.8b00406
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Hp-s1 Analogue Inhibits Amyloidogenic Toxicity in Alzheimer’s Disease Model Cells

Abstract: Alzheimer’s disease (AD) is characterized by extracellular deposition of amyloid plaques, which are predominantly composed of amyloid-β (Aβ) peptide derived from amyloid precursor protein (APP) cleavage. APP interacts with tropomyosin receptor kinase A, a neurotrophic receptor associated with gangliosides and mediating neuronal survival and differentiation through the extracellular signal-regulated protein kinase (ERK) pathway. The ganglioside Hp-s1’s analogue Hp-s1A exerts neuritogenic activity; however, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In addition, administration of naked GM1 can decrease binding of amyloid fragments to neuronal lipid rafts [ 156 ]. Moreover, gangliosides may inhibit amyloidogenic processing of APP [ 180 ].…”
Section: Gangliosides and Aβmentioning
confidence: 99%
“…In addition, administration of naked GM1 can decrease binding of amyloid fragments to neuronal lipid rafts [ 156 ]. Moreover, gangliosides may inhibit amyloidogenic processing of APP [ 180 ].…”
Section: Gangliosides and Aβmentioning
confidence: 99%
“…It is worth noting that Hp-s1 alone increased the phosphorylation of ERK in microglial cells. Several previous studies reported that some gangliosides increase the phosphorylation of ERK, such as GM1 [ 36 ], Hp-s1 analog [ 23 ], and GM3 [ 37 ]. Increase in phosphorylation of ERK by Hp-s1 might explain why Hp-s1 cannot inhibit ERK activity in LPS-stimulated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…The neuritogenic activity of Hp-s1 and its synthetic analogs is better than that of GM1 ganglioside in PC-12 cells [ 22 ]. Moreover, Hp-s1 analog inhibits amyloidogenic toxicity in model cells of Alzheimer’s disease [ 23 ]. However, the effects of Hp-s1 on neuroinflammation are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…N2A cells (ATCC, CCL-131) were maintained in minimum essential medium (Eagle) with 2 mM L-glutamine, 0.1 mM non-essential amino acids, 1.5 g/L sodium bicarbonate, and 1.0 mM sodium pyruvate (Life Technologies, Carlsbad, CA, United States), supplemented with 10% heat-inactivated fetal bovine serum (Life Technologies), 100 units/mL penicillin, 100 μg/mL streptomycin, and 2.5 μg/mL amphotericin B (Life Technologies) as indicated [ 51 , 52 ]. Cultures were incubated at 37 °C with 5% CO 2 in a humidified incubator.…”
Section: Methodsmentioning
confidence: 99%